A 60 GHz CMOS Power Amplifier for Wireless Communications - Tuan Anh Vu (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents a 60 GHz power amplifier (PA) suitable for wireless communications. The two-stage wideband PA is fabricated in 55 nm CMOS. Measurement results show that the PA obtains a peak gain of 16 dB over a -3 dB bandwidth from 57 GHz to 67 GHz. It archives an output 1 dB compression point (OP1dB) of 4 dbm and a peak power added efficiency (PAE) of 12.6%. The PA consumes a total DC power of 38.3 mW from a 1.2 V supply voltage while its core occupies a chip area of 0.45 mm2.